Early supplement of probiotics reduces the risk of obesity among preschool children: a real-world observational study - Zhang, Maolin; Ding, Liwen; Strodl, Esben; Yin, Xiaona; Wen, Guomin; Sun, Dengli; Xian, Danxia; Zhao, Yafen; Zheng, Yuxing; Liu, Feitong; Hu, Ruibiao; Zhao, Lingling; et al. (Frontiers in Nutrition, 2025)
IntroductionRecent studies have mainly focused on the relationship between probiotic supplementation and childhood obesity in infancy and school-age periods, with a lack of research on preschool stage (3–7 years). This study aimed to explore whether early childhood supplementation with probiotics (0–3 years) could reduce the risk of overweight and obesity among preschoolers.MethodsA cross-sectional survey was conducted in 2022 among preschoolers from Longhua District, Shenzhen, China. Their mothers were asked to complete a structured questionnaire regarding socio-demographic details and probiotic supplementation of children during the first 0–3 years. Trained professionals measured the children’s current weight and height. Childhood obesity was defined as the body mass index (BMI) being at or above the cut-offs for age and sex according to the BMI growth curves for Chinese children. Multinomial logistic regression analysis was conducted to explore the relationship between probiotic supplementation in children aged 0–3 years and preschool overweight and obesity with controlling for potential confounders. Sex differences, gestational age differences, and birth weight differences were analyzed.ResultsAmong the 31,190 children included, 1,389 were classified as obese and 4,337 as overweight. After controlling for potential confounding factors, multinomial logistic regression analysis suggested that probiotic supplementation during the period of age 0–3 years was associated with a lower likelihood of being overweight (AOR = 0.88, 95% CI = 0.82 ~ 0.95) or obesity (AOR = 0.82, 95% CI = 0.72 ~ 0.93). Children who consumed a probiotic product containing Bifidobacterium longum subsp. infantis R0033, Bifidobacterium bifidum R0071, and Lactobacillus helveticus R0052 had a lower risk of being overweight (AOR = 0.88, 95% CI = 0.80 ~ 0.96) or obese (AOR = 0.85, 95% CI = 0.73 ~ 0.98). Further stratified analyses showed a significant association with a lower likelihood of obesity only in girls (AOR = 0.70, 95% CI = 0.56 ~ 0.88), but no significant association was observed in boys (AOR = 0.88, 95% CI = 0.75 ~ 1.02).DiscussionProbiotic supplementation in children aged 0–3 years was associated with a lower risk of overweight and obesity in preschool children, with a potential gender difference. These findings highlight the potential role of early probiotic supplementation in children for preventing overweight and obesity.